Factors associated with financial restatements: evidence from Malaysia - Suhaily Hasnan; Alfiatul Rohmah Hussain (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examines seven factors associated with financial restatements in Malaysian publicly listed companies (PLCs). We hypothesize that two factors proxy for management rationalization, two for management motives and three for the opportunity to predict financial restatements. Our sample consists of 85 restatement firms and 85 no-restatement firms, listed on the Bursa Malaysia and have a complete set of data from 2005-2011. The objective of this study is to examine how rationalization, motive and weak governance lead to financial restatements in emerging economies, like Malaysia. With regard to rationalization, we find that founders are negatively and significantly associated with financial restatements while related party transactions (RPTs) are positively and significantly associated. Additionally, we find evidence that opportunity for restatement proxied by audit quality is negatively and significantly associated with financial restatements.